Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1136/emj.2006.043943
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative practices in unscheduled emergency care: role and impact of the emergency care practitioner qualitative and summative findings

Abstract: Objective: To identify collaborative instances and hindrances and to produce a model of collaborative practice. Methods: A 12-month (2005)(2006) mixed methods clinical case study was carried out in a large UK ambulance trust. Collaboration was measured through direct observational ratings of communication skills, teamwork and leadership with 24 multi-professional emergency care practitioners (ECPs), interviews with 45 ECPs and stakeholders, and an audit of 611 patients Results: Using a generic qualitative appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…Across the world there are differing scope of practice limitations and cultural, communication and collaborative issues. For example, Cooper et al (2007a) identified cultural issues such as blue collar 'crew room' perspectives versus white collar professionalism; restricted ambulance codes of communication compared to the elaborate communication codes in medicine; varying educational levels; and poor collaborative links between, for example, health and social services. O'Meara (2003) also recognised the barriers to the development of such roles including education, attitude change, and relaxation of professional boundaries, issues which Cooper et al (2007a) suggest may be resolved in part, by appointment of clinical leads, degree level training, clinical supervision, and focussed task allocation/ dispatch.…”
Section: Discussionmentioning
confidence: 99%
“…Across the world there are differing scope of practice limitations and cultural, communication and collaborative issues. For example, Cooper et al (2007a) identified cultural issues such as blue collar 'crew room' perspectives versus white collar professionalism; restricted ambulance codes of communication compared to the elaborate communication codes in medicine; varying educational levels; and poor collaborative links between, for example, health and social services. O'Meara (2003) also recognised the barriers to the development of such roles including education, attitude change, and relaxation of professional boundaries, issues which Cooper et al (2007a) suggest may be resolved in part, by appointment of clinical leads, degree level training, clinical supervision, and focussed task allocation/ dispatch.…”
Section: Discussionmentioning
confidence: 99%
“…At the 5% level, there was no statistically significant association between the mean knowledge level and the occupation (p=0.094), although drivers had a lower rate of correct answers in most questions. It can be inferred that the workload often keeps workers from consulting the guidelines and implementing them in their practice (9)(10) .…”
Section: Discussionmentioning
confidence: 99%
“…Segundo o Centers for Disease Control and Prevention, qualquer trabalhador em serviços de emergência, e cujo trabalho exige contato com sangue ou outros fluidos corporais deve receber informações sobre biossegurança durante o horário de trabalho e participar de cursos anuais (3,13) . Além disso, programas que visem educação em serviço devem ser incentivados, desenvolvidos e implementados com a finalidade de reduzir as diferenças individuais de conhecimento entre a equipe de saúde (3) .…”
Section: Resultsunclassified